2019
DOI: 10.1111/jth.14480
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated intravascular coagulation in cardiac arrest and resuscitation

Abstract: The aims of this review are to demonstrate that the changes in coagulation and fibrinolysis observed in cardiac arrest and resuscitation can be recognized as disseminated intravascular coagulation (DIC), and to discuss the probability of DIC being a therapeutic target. The appearance of triggers of DIC, such as damage-associated molecular patterns, inflammatory cytokines, and adrenaline, is associated with platelet activation, marked thrombin generation and fibrin formation, insufficient anticoagulation pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 102 publications
4
38
0
6
Order By: Relevance
“…Accordingly, the unfavorable neurologic outcome is attributed to the cerebral microvascular occlusion that causes the no-re ow phenomenon [31]. Many animal and clinical studies demonstrated a more severe degree of microvascular changes is associated with poor outcomes including severe hypoxic brain injury, immediate death without ROSC, and high mortality [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the unfavorable neurologic outcome is attributed to the cerebral microvascular occlusion that causes the no-re ow phenomenon [31]. Many animal and clinical studies demonstrated a more severe degree of microvascular changes is associated with poor outcomes including severe hypoxic brain injury, immediate death without ROSC, and high mortality [32].…”
Section: Discussionmentioning
confidence: 99%
“…In patients who achieve ROSC after CA, PCAS mimics the immunologic and coagulation disorders in severe sepsis [8]. the development of disseminated intravascular coagulation (DIC) as a serious disease results in an increased tendency of bleeding, microvascular thrombosis, thrombocytopenia, and multiple organ dysfunction, consequently affecting the clinically unfavorable outcomes of patients with PCAS [32]. DIC and TMA show similar laboratory ndings and presenting symptoms [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deswegen imponiert die DIC regelhaft (manche Autoren konstatieren "immer" [7] als thrombotische Koagulopathie.…”
Section: Merkeunclassified
“…Unter physiologischen Bedingungen verhindert u. a. das Enzym Plasminogen-Aktivator-Inhibitor-1 (PAI-1) durch Bindung von tPA dessen unkontrollierte Wirkung auf Plasminogen. Einen durch Ischämie/Reperfusion ausgelösten schnellen Anstieg der tPA-Konzentration kann jedoch PAI-1 nicht zeitnah kompensieren, weil dessen Synthese und Freisetzung mehrere Stunden (4-6 h) in Anspruch nimmt [7]. Zweiphasiger Verlauf der Fibrinolysestörung Die Störung des fibrinolytischen Systems bei DIC kann demnach zweizeitig verlaufen.…”
Section: Dic Mit Fibrinolytischem Phänotypunclassified